Single-donor (apheresis) platelets and pooled whole-blood-derived platelets--significance and assessment of both blood products - Hitzler, Walter E (Clinical laboratory (Heidelberg), 2014)
The transfusion efficacy of ATK, which contain fully functional platelets, is beyond all doubt. The equivalence of ATK and PTK has been subject of many studies. Some of those studies show the superiority of ATK's, while others do not, but there have been no studies that demonstrated a superiority of PTK's. The superiority of platelets stored in plasma and in third generation additive solution was demonstrated in clinical studies; therefore, it cannot be said that all the platelet concentrates on the German market are equivalent in efficacy. Of decisive importance, above all, is the risk of transfusion-transmitted infections with known pathogens, or those not yet discovered. This risk is different for ATK compared to PTK. Taking this difference in risk and the difference in donor exposure of transfused patients into account, it can definitely be said that ATK and PTK are not equivalent. In 2012, the Robert-Koch-Institute (RKI) published a mathematical risk model for different platelet concentrates and assessed the risk of transmitting known pathogens such as HIV, HCV, and HBV. The risk was higher for PTK compared to ATK. The relative risks for PTK derived from 4BCs were 2.2 (95%--CI: 2.1-2.4) for HIV, 2.7 (95%--CI: 2.5-3.0) for HCV, and 2.2 (95%--CI: 2.8-3.7) for HBV. At the present time, these are the relative risks of transfusion-transmitted infections with the traditional pathogens for PTK compared to ATK. In addition to the RKI assessed risks, there is the theoretical risk of a new, unknown agent, transmitted through blood exposure. The magnitude of this risk is hardly predictable for PTK. The experience gathered so far, especially in the last three decades, with the emergence of HIV, prions, and West Nil virus, shows that the biological nature of a next transfusion-transmissible infectious agent cannot be predictable. This agent, if we think at a conventional sexually transmissible agent with nucleic acid and long latent period, would spread first in areas with high population density and thereby reduce the theoretical advantage of ATK (but definitely would not nullify it!). It is equally plausible, however, that this agent would behave like a prion, non-sexual transmission, or like a West-Nil virus, a non-contagious vector-transmitted agent. For PTK this would mean a relative risk up to 4 times (PTK from 4 BCs) or 5 times (PTK from 5 BCs) higher than the risk estimated by the Robert-Koch-Institute. If, taking the passive surveillance data and the changing variables (donor frequency, donor population, and donor location) into account, the risk of transmission of an infection via ATK (exposure to 1 donor) with HIV, HCV, and HBV moves closer to the higher risk of PTK (exposure to 4 or 8 donors, in case of double ATK per patient), this result of the risk model calculation by no means indicates any equivalency between PTK and ATK with respect to the risk of transmission of infection. The modifiable variables of donor frequency, donor population, and donor location need to be modified, as scientific deductions, in such a way that the avoidable risk of ATK which is influenced by these variables can be corrected to the minimum risk of a transmission of infection of HIV, HBV, and HCV via ATK in comparison to PTK. The minimum risk of a possible transmission of infection via ATK (exposure to 1 donor) is the basic intrinsic risk of each individual blood donation. The basic intrinsic risk increases relative to the number of blood donations or exposure to donors (PtK has an unalterable, production-dependent exposure to 4 or 8 donors). Let us consider a 1:1.000 prevalence for a new pathogen, which is spread equally in each donor population (apheresis and whole blood) and the present case of approximately 500,000 transfused platelet concentrates in Germany. This means that for the production of 4 PTK about 2 million donations are processed, 2,000 infectious Buffy-Coats are obtained and, thereby, 2,000 infectious PTK. In the case of ATK, considering five (5) donations per year, theoretically, it would mean 100 donors infected and 500 infectious ATK. Considering 15 apheresis donations per donor per year, this would mean that 33 donors are infected, but still 500 infectious ATK would be produced. The prion is an example of a pathogen that, although its existence is well known, cannot be proven or pathogen-reduced. In addition, it has a very long incubation period compared to the donation intervals. Due to the manufacturing process, PTK has a 4-fold higher donor exposure and therefore a 4-fold higher risk for transfusion-transmitted infections compared to ATK. If a patient needs the transfusion of two platelet concentrates, by transfusing a double-ATK from the same donor the risk of transfusion-transmitted infections will remain the same. On the other hand, the risk will increase by 8-fold by transfusing two PTK. The only current possibility to prevent or to minimize the risk of infection with prions is to minimize the donor exposure by transfusing ATK instead of PTK. Hypothetical risk scenarios carry significant weight in law. This can be seen in the constant rulings of the German Federal Supreme Court (Bundesgerichtshofs (BGH)) on the so-called hypothetical risk explanations (BGH, NJW 1996, 776, 777; 2000, 1784, 1787; 2005, 2614, 2616). Therefore, a risk does not need to be confirmed to be subject to compulsory explanation. It is sufficient that serious voices in the medical scientific community point to specific risks, which cannot be set aside as insignificant outside opinions, but must be viewed as serious warnings. According to the rulings, patients must even be informed of rare and often extremely rare risks, which could, should they come true, significantly impact daily life and, despite their rarity, are specific to the treatment and are startling for the ordinary person (BGH, 15.02.2000- VI ZR 48199 -; BGH, 30.11.2004 - VI ZR 209104 -; OLG Hamm, 29.09.2010 - 1-3 V 169109). These conditions have been fulfilled for PTK according to current knowledge, especially since, in the meantime in several rulings, the federal supreme court has required the reference to as yet unknown risks (refer to BGH, 13.06.2006 - VI ZR 323104 - for the use of new medical treatment methods, BGH, 27.06.2007 - VI ZR 55105 for experimental therapy using new, unapproved medication BGH, 06.07.2010 - VI ZR 198109 - for unknown risks cannot be excluded, for example based on anatomical conditions). ATK and PTK are therapeutic alternatives with the same range of indications for treatment using thrombocytes, however, with differing risks of infection, with different exposures to donors, and with different efficacy. ATK and PTK. ATK and PTK are therapeutic alternatives in terms of pharmaceutical law based on the different risks and the different quality. Patients must be informed of therapeutic alternatives such as ATK and PTK according to the patient rights law. Denial of reimbursement for additional fees for ATK by individual insurance companies (or paying authorities) deviates blatantly, as seen in the ruling of the Social Court of of the Saarland in this matter, from the basic requirement of the Transfusion Law (Transfusionsgesetz (TFG)) and is legally incorrect. The legality of the question whether the transfusion of ATK is indicated or if PTK had sufficed, is not allowable within the context of an MDK-Test according to subsection 275 ff. SGB V. The denial is a direct infringment on the treatment authority of the attending hospital physician and is illegal according to subsection 275 Abs. 5 SGBV. It is certainly possible to establish a full ATK supply and can be immediately realized by increasing donation rates from 5 to 8.3 apheresis donations per year in the current scenario of apheresis structure and donor population. The donation interval between two apheresis donations would be 49 days. A complete supply with ATK can also be immediately implemented by enlarging the donor population, keeping the current apheresis donation frequency. The donor pool must be increased by 24,576 donors, which means a 67% increase of the existing donor population. A transition to an ATK supply that can cover the entire demand can certainly be realized in a short period of time, while assuring a complete supply with PTK is not a realistic option. All existing studies advise taking extreme caution with any alternative to the current German gold standard for the treatment of hyporegenerative thrombocytopenia. A prophylactic transfusion of a non-pathogen-inactivated platelet concentrate with on average 3 x 10(11) platelets is recommended when the platelet count drops below the threshold of 10,000/microL. All other alternatives to this strategy show an increase in intracranial bleeding events. The existing studies on platelet dose (PLADO-Trial and StoP-Trial) do not recommend deviating from 3 x 10(11) platelets per unit. On the contrary, these studies demonstrate that the only practicable way is to individually correlate every platelet transfusion to the patient body surface. Considering the current knowledge, it is not justified to lower the standard dose and, for certain patient groups, to switch from prophylaxis to therapeutic platelet transfusion. Applying ATK or PTK with a lower platelet content and only for therapeutic purposes, could considerably increase the bleeding risk, especially for WHO grades III and IV. This will also affect all the patients who receive an induction treatment. Through pathogen reduction, in parallel with platelet loss (Apoptosis), the function of the treated platelets is impaired. Alternatively, the cell destruction caused during this process could result in a release of platelet microRNA directly into the supernatant or in microvesicles. This reduction of microRNA will affect the storage of the platelets. (ABSTRACT TRUNCATED)